ANALISIS DESAIN KEMASAN GARAM MANDI (Bath Salt) DENGAN MENGGUNAKAN METODE VALUE ENGINEERING - Nurul Fabrianita; Iffan Maflahah; M Fuad Fauzul Mu'tamar; Dian Farida Asfan (Jurnal Agroindustri, 2023)
Bath salts are shaped like scrubs or scrubs usually used when bathing. Bath salts are made with the main ingredient Epsom. This bath salt has a bright white color. The public needs to learn about Bath salts. To be able to introduce a new product, it is necessary to do a market analysis of the product, including packaging. One of the attractions of consumers to products is the packaging. This research aims to identify consumer choice criteria for designing bath salt packaging and to analyze alternative packaging options using value engineering to obtain bath salt packaging design performance. The research stages are the information stage, the creation stage, the analysis stage, the development stage, and the recommendation stage. The information stage in obtaining the order of importance is packaging materials, labels, shapes, graphic designs, and ease of use of packaging. The inventive step determines the specifications used in designing bath salt packaging. The analysis phase is carried out on three components, namely, performance analysis, cost analysis, and value analysis. The development stage is carried out to determine the best alternative concept. The bath salt packaging design that suits the needs and desires of consumers is a jar-shaped glass material packaging; the lid has a yellowish-green label, the bottom has a white label with yellowish-green writing, the dimensions of the package are (height 5.3 cm and diameter 9.3 cm), and the label section contains information about the product name, brand, company name, net weight, composition, BPOM, method of use, barcode, expiration date.